Structural and temporal dynamics analysis of zinc-based biomaterials: History, research hotspots and emerging trends - Kunshan Yuan; Chengchen Deng; Lili Tan; Xiangxiu Wang; Wenhua Yan; Xiaozhen Dai; Ruolin Du; Yufeng Zheng; Haijun Zhang; Guixue Wang (Bioactive Materials, 2024)
Objectives: To examine the 16-year developmental history, research hotspots, and emerging trends of zinc-based biodegradable metallic materials from the perspective of structural and temporal dynamics. Methods: The literature on zinc-based biodegradable metallic materials in WoSCC was searched. Historical characteristics, the evolution of active topics and development trends in the field of zinc-based biodegradable metallic materials were analyzed using the bibliometric tools CiteSpace and HistCite. Results: Over the past 16 years, the field of zinc-based biodegradable metal materials has remained in a hotspot stage, with extensive scientific collaboration. In addition, there are 45 subject categories and 51 keywords in different research periods, and 80 papers experience citation bursts. Keyword clustering anchored 3 emerging research subfields, namely, #1 plastic deformation #4 additive manufacturing #5 surface modification. The keyword alluvial map shows that the longest-lasting research concepts in the field are mechanical property, microstructure, corrosion behavior, etc., and emerging keywords are additive manufacturing, surface modification, dynamic recrystallization, etc. The most recent research on reference clustering has six subfields. Namely, #0 microstructure, #2 sem, #3 additive manufacturing, #4 laser powder bed fusion, #5 implant, and #7 Zn–1Mg. Conclusion: The results of the bibliometric study provide the current status and trends of research on zinc-based biodegradable metallic materials, which can help researchers identify hot spots and explore new research directions in the field.